Comunicación con Imágenes, Fotografía participativa para visualizar el imaginario de violencia en niños y niñas de grado segundo - A jornada tarde de la Institución Educativa Pio XII del Municipio de Mocoa del Departamento d Putumayo, Colombia. (2016)
This research project assumes a methodology of action research and participatory involvement with photography that sought to show realities and promote change for social improvement. This research addressed a pediatric population of children in second grade of School Pio XII City Mocoa, Putumayo. He sought to show the imagination of this population about violence through shooting and a role play in which they were the ones who captured images; also were the protagonists of the scene and sought recognize looks, identify the types of violence and make a contribution to education on this topic and methodology.